6 | ( | 2 | ÷ | 3 | × | x | − | 5 | ) | − | x | = | 6 | − | ( | 1 | ÷ | 2 | × | x | + | 1 | ) |
方程左边 = | 6 | × | 2 | ÷ | 3 | × | x | − | 6 | × | 5 | − | x |
= | 4 | x | − | 30 | − | x |
= | 3 | x | − | 30 |
3 | x | − | 30 | = | 6 | − | ( | 1 | ÷ | 2 | × | x | + | 1 | ) |
方程右边 = | 6 | − | 1 | ÷ | 2 | × | x | − | 1 |
= | 6 | − | 1 2 | x | − | 1 |
= | 5 | − | 1 2 | x |
3 | x | − | 30 | = | 5 | − | 1 2 | x |
3 | x | + | 1 2 | x | = | 5 | + | 30 |
7 2 | x | = | 5 | + | 30 |
7 2 | x | = | 35 |
x | = | 35 | ÷ | 7 2 |
= | 35 | × | 2 7 |
= | 5 | × | 2 |
x | = | 10 |